The C.R.E.W. (Concerned Resource & Environmental Workers): A Service Learning Research Project - Aguilar, Jonathan; Cortes, Viviana; De La Huerta, Aubrey; Duran, Marco; Flores, Darlene; Gainey, Megan; Gonzalez, Jasmine; Gonzalez, Liliana; Juarez, Omar; Melgar, Nuria; Rincon, Ana; Rodriguez, Tiffany; et al. (CBR@CSUCI: An annual volume of community-based research, 2025)
EXECUTIVE SUMMARY This report is based on research conducted by Sociology students from California State University, Channel Islands. The research was administered through an online survey that was emailed to supporters/volunteers of The C.R.E.W. The survey was a mix of open and closed-ended questions with about 87 respondents. Supporter Demographics: Most of the respondents from The C.R.E.W. come from the Ojai area (78%) which can explain why respondents are influenced by The C.R.E.W. and their work within their communities, and are around the ages of 61-80 years old (56.81%). We also had a few supporters from the ages of 21-40 years old (4.60%). Patterns of Satisfaction & Preference: Most respondents have been supporting The C.R.E.W from one to five years (29.89%). In addition to most of them being ‘very likely’ to continue being a supporter of The C.R.E.W. (74.71%). Furthermore, most respondents were ‘satisfied’ with The C.R.E.W.’s outreach and cultivation of community partnerships. Patterns of Respondents: Most of the respondents are affiliated with The C.R.E.W. through being donors and viewing the organization as aiding in youth employment. Additionally, most respondents felt inclined to support both employment development, and conservation purposes. Respondent awareness of The C.R.E.W: Most respondents were familiar with specific projects involving The C.R.E.W (73.56%). As well as most respondents felt that The C.R.E.W upheld both its mission pillars: ‘developing young leaders’ and ‘caring for the environment’. Differences in Patterns of Respondents: Besides supporters being aware of The C.R.E.W. through direct contact/work, some respondents heard about them through word of mouth or news outlets. Furthermore, the impact of the environmental work that The C.R.E.W. provides aids in community satisfaction and can increase the number of supporters. Additional attractions and Broader Implications: The C.R.E.W are mostly known for their environmental work involving restoration projects and clearing hiking trails. In the future supporters would like to see The C.R.E.W. providing broader services that can include educating the public, and younger kids about the environment. Additionally, the continuance of collaborating with nonprofits and community enrichment as well as further training and skill development with fire preparedness.